What Drives Public Debt Growth? A Focus on Natural Resources, Sustainability and Development - Mammadli, Mubariz; Sadik-Zada, Elkhan Richard; Gatto, Andrea; Huseynova, Rana (International Journal of Energy Economics and Policy, 2021)
Public debt is a notable measure of economic and financial sustainability which encountered policy and scholarly interest in the international development ambients. This paper investigates the major drivers of public debt growth in 184 countries. The underlying cross-country survey is conducted on the basis of the improved compilation of datasets on the central government debt for 2013. The study finds that oil abundance, economic growth rate, the share of mineral rent in the total revenue, interest rate payments for foreign borrowings, and being a developing country have a statistically significant impact on the growth of the public debt. In contrast, defence spending, unemployment rate, and inflation rate do not have a statistically significant positive impact on the public debt rate. Keywords: Public Debt, Natural Resources, Sustainability, Oil Rent, Mineral Rent, Defence Spending, Developing Countries JEL Classifications: F21, F34, F36, G15, H6, N1, F3 DOI: https://doi.org/10.32479/ijeep.10901